High-stability composite latex as well as preparation method and application thereof
By optimizing the process flow, dissolving, emulsifying, distilling and centrifuging, a high stability composite latex is formed, which solves the mechanical stability and long-term storage problems of self-adhesive bandage latex, and achieves high stability and good viscosity of latex.
Patent Information
- Application Number
- CN202411949696.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-25
AI Technical Summary
The existing self-adhesive bandage latex has problems with mechanical stability and long-term storage, which are prone to layering and mildew, and traditional methods cannot completely solve these problems.
By optimizing the process flow, polyisoprene rubber and tackifier are first dissolved, followed by emulsification, distillation and centrifugation to form a highly stable composite latex. This method ensures that the polyisoprene rubber and tackifier form stable colloidal particles in the emulsification system to avoid stratification.
It achieves high mechanical stability and long-term storage capacity of composite latex, effectively prevents stratification and mold, and is suitable for medical materials that require good viscosity and stability.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of chemical polymer materials, and in particular to a high-stability composite latex and a preparation method and application thereof. Background Art
[0002] Self-adhesive bandages are widely used in the medical field. The current base material is mainly natural latex, and a certain amount of tackifier emulsion is compounded to meet the application requirements of self-adhesive bandages. However, the presence of protein in natural latex can easily cause human allergies, and the inconsistency of the emulsification system of natural latex and tackifier emulsion. After the two are compounded, they are prone to poor mechanical stability, easy stratification, mildew and other problems. The traditional method is to improve stability by adding ammonia water, but the introduction of ammonia water has a certain pungent smell, which is very unfriendly to users, and cannot completely solve the problem of poor stability.
[0003] The main component of natural latex is polyisoprene. Currently, the use of polyisoprene latex as a base material can effectively avoid allergies caused by protein, but when it is compounded with a thickener emulsion, the above-mentioned problems such as poor mechanical stability, easy stratification and mildew still exist. The main reason is that the emulsification system of polyisoprene latex and the emulsification system of the thickener emulsion are inconsistent, resulting in changes in the lipophilicity and hydrophilicity and pH value of the emulsification system after compounding, which in turn affects the overall stability of the latex.
[0004] At present, whether using natural latex or polyisoprene latex, the traditional method in the industry is to use polyisoprene latex and tackifier emulsion for compounding. This method cannot fundamentally solve the stability problem. There are two construction methods for self-adhesive bandages, one is rolling and the other is spraying. If the stability is poor, gel will appear during the construction process, affecting the uniformity of rolling glue and easily clogging the nozzle during spraying. Therefore, the stability of the composite latex is a very important factor. Summary of the invention
[0005] The object of the present invention is to provide a high-stability composite latex and a preparation method and application thereof, so as to solve the problems raised in the above background technology.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] A method for preparing a high-stability composite latex, characterized in that it comprises the following steps:
[0008] Step 1: Dissolving, mixing the solvent and the solid raw material in a weight ratio of 8-12:1, preferably 10:1, and dissolving under mechanical stirring at 200-400 rpm for 24-48 hours, preferably 36 hours, to prepare a glue solution, wherein the prepared glue solution is uniform and transparent without solid matter;
[0009] Step 2: emulsification, adding an emulsifier, a stabilizer, a chelating agent and a pH regulator into deionized water respectively, stirring to dissolve, then adding the dissolved mixture into the glue prepared in step 1, and then adding the nanofiller, stirring quickly until it is in an emulsion state, and then homogenizing and emulsifying at 6000-12000 r / min for 30-90 minutes to prepare an emulsion; preferably, the equipment used is a homogenizing emulsifier, the rotation speed is most preferably 10000 r / min, and the emulsification time is most preferably 60 minutes;
[0010] Step 3: Distillation: The emulsion prepared in the emulsification step is heated to 60-80°C for atmospheric distillation and vacuum distillation to remove the solvent component in the emulsion. The atmospheric distillation time is 4-6 hours, and the vacuum distillation time is 1-2 hours.
[0011] Step 4: Centrifugation, concentrate the distilled emulsion under high-speed centrifugation at 6000-10000 r / min for 5-20 min. After centrifugation, take the upper light liquid as the obtained composite latex; preferably, the equipment used is a high-speed centrifuge, and the most preferred centrifugation time is 15 min.
[0012] Preferably, in step 1, the solid raw material comprises polyisoprene rubber and a tackifier, in which, by weight, the polyisoprene rubber is 80-99 parts and the tackifier is 1-20 parts, and most preferably, the tackifier is 5-10 parts;
[0013] Preferably, the polyisoprene rubber includes rare earth rubber, titanium rubber and lithium rubber, and most preferably is titanium rubber.
[0014] Preferably, in step 1, the solvent used is cyclohexane or n-hexane.
[0015] Preferably, in step 2, the weight ratio of the deionized water to the glue solution is 0.8-1:1.
[0016] Preferably, based on the total weight of the solid raw materials, the proportion of each component added to the total weight is: emulsifier 3%-10%, stabilizer 1%-5%, pH adjuster 0.5%-2%, chelating agent 0.5%-2%, nanomaterial 0.1%-1%, and most preferably, emulsifier 5%-8%, stabilizer 1%-3%.
[0017] Preferably, the tackifier includes one or more of phenolic resin, terpene resin, rosin resin, and SIS rubber.
[0018] Preferably, the emulsifier is an anionic emulsifier, including one or more of potassium disproportionate rosin acid, sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, sodium dodecyl sulfonate, potassium oleate, and sodium secondary alkyl sulfonate, and most preferably, one or two of potassium disproportionate rosin acid, sodium dodecyl sulfate, and potassium oleate are used in combination; the stabilizer is a nonionic emulsifier, including one or more of the fatty alcohol polyoxyethylene ether series; the pH adjuster is sodium hydroxide or potassium hydroxide; the chelating agent is one or more of sodium tripolyphosphate, sodium hexametaphosphate, disodium EDTA, and sodium citrate; and the nanofiller is nano-silicon dioxide or nano-calcium carbonate.
[0019] Another aspect of the present invention discloses a composite latex prepared by the method for preparing the high-stability composite latex described in any of the above technical solutions.
[0020] The invention also discloses application of the composite latex in a self-adhesive bandage.
[0021] The beneficial effects of the above technical solution of the present invention are as follows:
[0022] 1. This solution uses an optimized process flow to dissolve polyisoprene rubber and solid tackifier at the sol stage at the same time, and then undergoes emulsification, distillation and centrifugation steps in sequence to finally obtain a composite latex product. During the emulsification process, polyisoprene rubber and tackifier are dispersed in water by the emulsifier to form stable colloidal particles, ensuring that even if there is a difference in density between the two, stratification due to the density difference will not occur, maintaining the consistency of the emulsified system.
[0023] 2. In the composite latex prepared by this scheme, polyisoprene rubber and thickener are coated by the emulsifier in the same rubber particle, the emulsified system is uniform and stable, and has good mechanical stability, which enhances its ability to be stored for a long time and effectively prevents possible stratification or mildew. It is particularly suitable for medical materials such as self-adhesive bandages that require good viscosity and stability. DETAILED DESCRIPTION
[0024] In order to make the present application easier to understand, the present application will be further described in detail below in conjunction with the examples, which are merely illustrative and are not intended to limit the scope of application of the present application. The raw materials or components used in the present application can be obtained through commercial routes or conventional methods unless otherwise specified.
[0025] The stability test method of the composite latex of the present invention refers to SH / T 1151.1-2019 Synthetic rubber latex, determination of mechanical stability, part 1: high-speed method for determination.
[0026] Example 1
[0027] A high-stability composite latex and a preparation method thereof, comprising the following steps:
[0028] Step 1: Dissolution: 80 g of polyisoprene rubber and 20 g of phenolic resin are added to 1000 g of cyclohexane and stirred at 400 rpm to dissolve. After 36 hours of dissolution, the mixture becomes a uniform rubber solution.
[0029] Step 2: Emulsification, add 5g of potassium disproportionate rosin acid, 5g of sodium dodecylbenzene sulfonate, 1g of fatty alcohol polyoxyethylene ether, 1g of sodium hexametaphosphate, and 1g of potassium hydroxide into 1000g of deionized water, stir to dissolve, after dissolution is complete, add 1g of nano-silicon dioxide and deionized water solution to the glue, stir rapidly for 15min, then turn on the homogenizer, and emulsify at 10000r / min for 60min.
[0030] Step 3: Distillation: The emulsion in step 2 is heated to 80°C and distilled under normal pressure under stirring to remove the cyclohexane solvent. The distillation is carried out under normal pressure for 5 hours and then switched to negative pressure distillation for 1.5 hours.
[0031] Step 4: Centrifugation: put the distilled emulsion into a centrifuge tube and centrifuge it at 8000r / min for 15min. The upper light liquid is the obtained composite latex.
[0032] Deionized water was added to the obtained composite latex to adjust the solid content to 60%, and the mechanical stability was tested. The test data showed that the time was 1800s and the gel was 0.08g.
[0033] Example 2
[0034] A high-stability composite latex and a preparation method thereof, comprising the following steps:
[0035] Step 1: Dissolving: 90 g of polyisoprene rubber and 10 g of terpene resin are added to 1000 g of cyclohexane and stirred at 400 rpm to dissolve. After 36 hours of dissolution, the mixture becomes a uniform rubber solution.
[0036] Step 2: Emulsification, add 4g of potassium disproportionate rosin acid, 4g of sodium dodecyl sulfate, 1.5g of fatty alcohol polyoxyethylene ether, 1g of disodium EDTA, and 1g of potassium hydroxide to 1000g of deionized water, stir to dissolve, after dissolution, add 0.5g of nano calcium carbonate and deionized water solution to the glue, stir rapidly for 15min, then turn on the homogenizer and emulsify at 8000r / min for 60min.
[0037] Step 3: Distillation: The emulsion in step 2 is heated to 80°C and distilled under normal pressure under stirring to remove the cyclohexane solvent. The distillation is carried out under normal pressure for 5 hours and then switched to negative pressure distillation for 1.5 hours.
[0038] Step 4: Centrifugation: put the distilled emulsion into a centrifuge tube and centrifuge it at 8000r / min for 15min. The upper light liquid is the obtained composite latex.
[0039] Deionized water was added to the obtained composite latex to adjust the solid content to 60%, and the mechanical stability was tested. The test data showed that the gel lasted for 1800 seconds and weighed 0.20 g.
[0040] Example 3
[0041] A high-stability composite latex and a preparation method thereof, comprising the following steps:
[0042] Step 1: Dissolving: add 85g polyisoprene rubber and 15g rosin resin into 1100g n-hexane, stir and dissolve at 400r / min, and dissolve for 36 hours to form a uniform rubber solution.
[0043] Step 2: Emulsification, add 5g of potassium disproportionate rosin acid, 5g of potassium oleate, 2g of fatty alcohol polyoxyethylene ether, 1g of sodium hexametaphosphate, and 1g of sodium hydroxide into 1000g of deionized water, stir to dissolve, after dissolution is complete, add 0.1g of nano-silicon dioxide and deionized water solution to the glue, stir rapidly for 15min, then turn on the homogenizer, and emulsify at 10000r / min for 60min.
[0044] Step 3: Distillation: The emulsion in step 2 is heated to 60°C and distilled under normal pressure under stirring to remove the n-hexane solvent. The distillation is carried out under normal pressure for 6 hours and then switched to negative pressure distillation for 1.5 hours.
[0045] Step 4: Centrifugation: put the distilled emulsion into a centrifuge tube and centrifuge it at 8000r / min for 10 minutes. The upper light liquid is the obtained composite latex.
[0046] Deionized water was added to the obtained composite latex to adjust the solid content to 60%, and the mechanical stability was tested. The test data was 1800s and the gel was 0.25g.
[0047] Example 4
[0048] A high-stability composite latex and a preparation method thereof, comprising the following steps:
[0049] Step 1: Dissolution: 95 g polyisoprene rubber and 5 g SIS rubber are added to 1200 g cyclohexane and stirred at 200 r / min to dissolve. After dissolving for 36 hours, the mixture becomes a uniform rubber solution.
[0050] Step 2: Emulsification, add 2g of potassium disproportionate rosin acid, 1g of sodium secondary alkyl sulfonate, 3g of fatty alcohol polyoxyethylene ether, 1g of disodium EDTA, and 1.5g of potassium hydroxide to 1000g of deionized water, stir to dissolve, after dissolution is complete, add 1g of nano-silicon dioxide and deionized water solution to the glue, stir rapidly for 15min, then turn on the homogenizer, 6000r / min, and homogenize and emulsify for 90min.
[0051] Step 3: Distillation: The emulsion in step 2 is heated to 80°C and distilled under normal pressure under stirring to remove the cyclohexane solvent. The distillation is carried out under normal pressure for 6 hours and then switched to negative pressure distillation for 2 hours.
[0052] Step 4: Centrifugation: put the distilled emulsion into a centrifuge tube and centrifuge it at 10000r / min for 5 minutes. The upper light liquid is the obtained composite latex.
[0053] Deionized water was added to the obtained composite latex to adjust the solid content to 60%, and the mechanical stability was tested. The test data showed that the gel lasted for 1800 seconds and weighed 0.35 g.
[0054] Example 5
[0055] A high-stability composite latex and a preparation method thereof, comprising the following steps:
[0056] Step 1: Dissolving: add 90g polyisoprene rubber, 5g SIS rubber and 5g rosin resin into 900g n-hexane, stir and dissolve at 300r / min, and dissolve for 36 hours to form a uniform rubber solution.
[0057] Step 2: Emulsification, add 3g of potassium disproportionate rosin acid, 3g of fatty alcohol polyoxyethylene ether, 1g of sodium citrate, and 1g of potassium hydroxide into 800g of deionized water, stir to dissolve, after dissolution is complete, add 1g of nano-silicon dioxide and deionized water solution to the glue, stir rapidly for 15 minutes, then turn on the homogenizer, 10000r / min, homogenize and emulsify for 45 minutes.
[0058] Step 3: Distillation: The emulsion in step 2 is heated to 80°C and distilled under normal pressure under stirring to remove the n-hexane solvent. The distillation is carried out under normal pressure for 6 hours and then switched to negative pressure distillation for 2 hours.
[0059] Step 4: Centrifugation: put the distilled emulsion into a centrifuge tube and perform high-speed centrifugation at 8000r / min for 20min. The upper light liquid is the obtained composite latex.
[0060] Deionized water was added to the obtained composite latex to adjust the solid content to 60%, and the mechanical stability was tested. The test data showed that the gel lasted for 1800 seconds and weighed 0.40 g.
[0061] Example 6
[0062] A high-stability composite latex and a preparation method thereof, comprising the following steps:
[0063] Step 1: Dissolve, using cyclohexane as solvent, add 80g polyisoprene rubber and 20g phenolic resin into 800g cyclohexane, stir and dissolve at 200r / min, and dissolve for 36 hours to become a uniform rubber solution.
[0064] Step 2: Emulsification, add 5g of potassium disproportionate rosin acid, 5g of sodium dodecylbenzene sulfonate, 1g of fatty alcohol polyoxyethylene ether, 1g of sodium hexametaphosphate, and 1g of sodium hydroxide into 800g of deionized water, stir to dissolve, after dissolution, add 1g of nano-silicon dioxide and deionized water solution to the glue, stir rapidly for 15min, then turn on the homogenizer and emulsify at 12000r / min for 30min.
[0065] Step 3: Distillation: The emulsion in step 2 is heated to 70°C and distilled under normal pressure under stirring to remove the cyclohexane solvent. The distillation is carried out under normal pressure for 4 hours and then switched to negative pressure distillation for 1 hour.
[0066] Step 4: Centrifugation: put the distilled emulsion into a centrifuge tube and perform high-speed centrifugation at 6000r / min for 20min. The upper light liquid is the obtained composite latex.
[0067] Deionized water was added to the obtained composite latex to adjust the solid content to 60%, and the mechanical stability was tested. The test data showed that the gel lasted for 1800 seconds and weighed 0.58 g.
[0068] Example 7
[0069] A high-stability composite latex and a preparation method thereof, comprising the following steps:
[0070] Step 1: Dissolving: add 80g polyisoprene rubber, 10g phenolic resin and 10g rosin resin into 1000g cyclohexane, stir and dissolve at 300r / min, and dissolve for 36 hours to form a uniform rubber solution.
[0071] Step 2: Emulsification, add 3g of potassium disproportionate rosin acid, 3g of sodium dodecylbenzene sulfonate, 1g of fatty alcohol polyoxyethylene ether, 1g of sodium hexametaphosphate, and 1g of potassium hydroxide into 1000g of deionized water, stir to dissolve, after dissolution, add 1g of nano calcium carbonate and deionized water solution to the glue, stir rapidly for 15min, then turn on the homogenizer and emulsify at 10000r / min for 60min.
[0072] Step 3: Distillation: The emulsion in step 2 is heated to 80°C and distilled under normal pressure under stirring to remove the cyclohexane solvent. The distillation is carried out under normal pressure for 5 hours and then switched to negative pressure distillation for 1.5 hours.
[0073] Step 4: Centrifugation: put the distilled emulsion into a centrifuge tube and centrifuge it at 8000r / min for 15min. The upper light liquid is the obtained composite latex.
[0074] Deionized water was added to the obtained composite latex to adjust the solid content to 60%, and the mechanical stability was tested. The test data was 1800s and the gel was 0.15g.
[0075] Example 8
[0076] A high-stability composite latex and a preparation method thereof, comprising the following steps:
[0077] Step 1: Dissolving: 80 g polyisoprene rubber, 10 g phenolic resin and 10 g terpene resin are added to 1000 g cyclohexane and stirred at 400 rpm to dissolve. After 36 hours of dissolution, the mixture becomes a uniform rubber solution.
[0078] Step 2: Emulsification, add 7g of potassium disproportionate rosin acid, 3g of sodium dodecyl sulfate, 1g of fatty alcohol polyoxyethylene ether, 1g of sodium citrate, and 1g of potassium hydroxide into 1000g of deionized water, stir to dissolve, after dissolution, add 1g of nano calcium carbonate and deionized water solution to the glue, stir rapidly for 15min, then turn on the homogenizer and emulsify at 10000r / min for 90min.
[0079] Step 3: Distillation: The emulsion in step 2 is heated to 80°C and distilled under normal pressure under stirring to remove the cyclohexane solvent. The distillation is carried out under normal pressure for 5 hours and then switched to negative pressure distillation for 1.5 hours.
[0080] Step 4: Centrifugation: put the distilled emulsion into a centrifuge tube and centrifuge it at 8000r / min for 15min. The upper light liquid is the obtained composite latex.
[0081] Deionized water was added to the obtained composite latex to adjust the solid content to 60%, and the mechanical stability was tested. The test data showed that the gel lasted for 1800 seconds and weighed 0.22 g.
[0082] Comparative Example 1
[0083] The difference between it and Example 1 is that:
[0084] The latex is prepared according to the method in step 1, wherein polyisoprene rubber is used as a raw material, no tackifier is added, and the amount of polyisoprene rubber added is 100 g to prepare the latex; then the prepared latex is compounded with rosin resin emulsion in a ratio of 90:10 to prepare a composite latex.
[0085] Deionized water was added to the obtained composite latex to adjust the solid content to 60%, and the mechanical stability was tested, and the mechanical stability was 450 seconds.
[0086] Comparative Example 2
[0087] The difference between it and Example 1 is that:
[0088] The latex is prepared according to the method in step 1, wherein polyisoprene rubber is used as a raw material, no tackifier is added, and the amount of polyisoprene rubber added is 100 g to prepare the latex; then the prepared latex is compounded with a phenolic resin emulsion in a ratio of 80:20 to prepare a composite latex.
[0089] Deionized water was added to the obtained composite latex to adjust the solid content to 60%, and the mechanical stability was tested, and the mechanical stability was 320s.
[0090] Analysis of results: By comparing the test results of Examples 1-8 with those of Comparative Examples 1-2, it can be seen that there are significant differences between the Examples and Comparative Examples in terms of mechanical stability and long-term storage performance. The composite latex samples in Comparative Examples 1-2 showed obvious instability within a shorter test time (450s and 320s, respectively), which indicates that they have lower tolerance in the face of mechanical stress and may be more prone to stratification. In contrast, the composite latex prepared by this scheme (Examples 1-8) was only observed to have slight gel formation after 1800s of mechanical stability testing, and the gel amount ranged from 0.08g to 0.58g. In addition, during long-term storage, these samples also demonstrated excellent anti-stratification capabilities, maintained good uniformity, and no signs of mildew were found.
[0091] In the traditional compounding method of composite latex, in the latex system after compounding, due to the inconsistency of the types of emulsifiers coated on the outside of rubber particles and thickener particles, the coated emulsifier may reorganize during the continuous movement and collision of particles, destroying the original equilibrium state and resulting in poor stability. At the same time, the density difference between rubber particles and thickener particles may lead to stratification, floating and other phenomena.
[0092] This solution uses an optimized process flow to dissolve polyisoprene rubber and solid tackifier at the sol stage at the same time, and then undergo emulsification, distillation and centrifugation steps in sequence to finally obtain a composite latex product. During the emulsification process, polyisoprene rubber and tackifier are dispersed in water by the emulsifier to form stable colloidal particles, ensuring that even if there is a difference in density between the two, stratification due to the density difference will not occur, maintaining the consistency of the emulsified system.
[0093] In the composite latex prepared by the scheme, polyisoprene rubber and tackifier are coated by the emulsifier in the same rubber particle, the emulsified system is uniform and stable, and has good mechanical stability, which enhances its ability to be stored for a long time and effectively prevents possible delamination or mildew. The composite latex is particularly suitable for medical materials such as self-adhesive bandages that require good viscosity and stability.
[0094] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Other modifications or equivalent substitutions made to the technical solution of the present invention by ordinary technicians in the field should be included in the scope of the claims of the present invention as long as they do not depart from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for preparing a high-stability composite latex, characterized in that: The following steps are involved: Step 1: Dissolving, mixing the solvent and the solid raw material in a weight ratio of 8-12:1, and dissolving under mechanical stirring at 200-400r / min for 24-48h to form a glue solution; Step 2: Emulsification, adding the emulsifier, stabilizer, chelating agent and pH adjuster into deionized water respectively, stirring to dissolve, then adding the dissolved mixture into the glue prepared in step 1, then adding the nanofiller, stirring quickly until it is in an emulsion state, and then homogenizing and emulsifying at 6000-12000r / min for 30-90min to prepare an emulsion; Step 3: Distillation: The emulsion prepared in the emulsification step is heated to 60-80°C for atmospheric distillation and vacuum distillation to remove the solvent component in the emulsion. The atmospheric distillation time is 4-6 hours, and the vacuum distillation time is 1-2 hours. Step 4: Centrifugation: concentrate the distilled emulsion under high-speed centrifugation at 6000-10000 r / min for 5-20 minutes. After the centrifugation is completed, the upper light liquid is taken as the obtained composite latex.
2. The method for preparing a high-stability composite latex according to claim 1, wherein: In step 1, the solid raw material includes polyisoprene rubber and a tackifier, and in parts by weight, the polyisoprene rubber is 80-99 parts and the tackifier is 1-20 parts.
3. The method for preparing a high-stability composite latex according to claim 1, wherein: In step 1, the solvent used is cyclohexane or n-hexane.
4. The method for preparing a high-stability composite latex according to claim 1, wherein: In step 2, the weight ratio of the deionized water to the glue solution is 0.8-1:
1.
5. The method for preparing a high-stability composite latex according to claim 1, characterized in that: Based on the total weight of the solid raw materials, the proportion of each component added to the total weight is: emulsifier 3%-10%, stabilizer 1%-5%, pH regulator 0.5%-2%, chelating agent 0.5%-2%, nano material 0.1%-1%.
6. The method for preparing a high-stability composite latex according to claim 2, wherein: The tackifier includes one or more of phenolic resin, terpene resin, rosin resin and SIS rubber.
7. The method for preparing a high-stability composite latex according to claim 5, characterized in that: The emulsifier is an anionic emulsifier, including one or more of potassium disproportionate rosin acid, sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, sodium dodecyl sulfonate, potassium oleate, and sodium secondary alkyl sulfonate; the stabilizer is a nonionic emulsifier, including one or more of a fatty alcohol polyoxyethylene ether series; the pH regulator is sodium hydroxide or potassium hydroxide; the chelating agent is one or more of sodium tripolyphosphate, sodium hexametaphosphate, disodium EDTA, and sodium citrate; and the nanofiller is nano silicon dioxide or nano calcium carbonate.
8. The composite latex prepared according to the method for preparing a high-stability composite latex according to any one of claims 1 to 7.
9. Use of the composite latex according to claim 8 in a self-adhesive bandage.